Evaluación de la biofijación de CO2 y producción de biomasa a partir de las microalgas bajo condiciones de fotobiorreactor a escala laboratorio (2018)
This work evaluated the biofixation of CO2 from the microalgae Chlorella vulgaris and Scenedesmus dimorphus, whit growth conditions in a photobiorreactor. It was determined two ranges of dioxide concentrations carbon (0-3) % y (6-9)%, photoperiod 12L: 12O and temperature (24 °C -25 °C). The CO2 was supplied to photobiorreactor by means of an auxiliary tank; the ranges of concentrations were controlled by the K-33 ICB sensor and they were monitored in a GasLab software. The biofixation of CO2 process done in three stage: cell growth, determination of dry biomass and statistic analysis. After this it was evidenced that the microalga Scenedesmus dimorphus presents a better biofixation regardless of the percentage of carbon dioxide that is supplied, obtaining as results for (0-3)% CO2 and (6-9)% CO2 a biofixation of 1.66 g * L-1 * day-1 and 2.25 g * L-1 * day-1 respectively. Also one checked from the statistic analysis that both the change of microalga and the change of the concentrations of carbon dioxide yes intervene in the biofixation.